2019
DOI: 10.3168/jds.2019-17067
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic ELISA based on DNA-directed gold nanoparticle growth for Cronobacter detection in powdered infant formula samples

Abstract: The traditional gold nanoparticle (AuNP) growthbased plasmonic ELISA (pELISA) strictly and directly controlled by reducing reagents can achieve high sensitivity, but it remains fragile toward the surrounding environment. This work developed a sandwich pELISA for Cronobacter detection in powdered infant formula samples by mediating AuNP growth through DNA. In this assay, DNA adsorbed on the surface of gold nanoseeds guided the anisotropic crystal growth with hydroxylamine as a reducing reagent, and the catalase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A visual change in ELISA coloration with varying concentrations of AuNPs was also observed in the work of Wu et al (2019), who developed a sandwich pELISA for Cronobacter detection in powdered infant formula samples, with a cutoff limit of 3 × 10 5 cfu/mL [ 30 ].…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…A visual change in ELISA coloration with varying concentrations of AuNPs was also observed in the work of Wu et al (2019), who developed a sandwich pELISA for Cronobacter detection in powdered infant formula samples, with a cutoff limit of 3 × 10 5 cfu/mL [ 30 ].…”
Section: Resultsmentioning
confidence: 73%
“…A visual change in ELISA coloration with varying concentrations of AuNPs was also observed in the work of Wu et al (2019), who developed a sandwich pELISA for Cronobacter detection in powdered infant formula samples, with a cutoff limit of 3 × 10 5 cfu/mL [30]. An analysis of the results revealed that when the sample was negative, it exhibited a red hue and higher absorbance than did the positive samples, which showed a purple tint.…”
Section: Detection Of Pcv2 In the Serum By Plasmonic Elisamentioning
confidence: 63%
“…[50][51][52][53][54] In addition, compared to the other reported nanoparticle-based ELISA sensing strategies, the developed method provides several other advantages including (i) easy integration with conventional ELISA schemes, wherein HRPlabeled detector antibodies are used, [55][56] (ii) elimination of false positive and negative signal due to autoaggregation of the nanoparticles, [57][58] (iii) the greater stability of the AuNRs towards temperature, light and the biological thiols as compared to silver nanoprisms, 59 and (iv) easy and simple as it does not require any conjugation or surface functionalization of the AuNRs. [60][61]…”
Section: Immunoassay and Detection Principlementioning
confidence: 99%
“…The bacterial culture method for C. sakazakii is a traditional method that takes 5 to 7 days to obtain results and cannot meet the needs for rapid detection and screening of bacteria. Some other methods that are classified into protein-based biosensing method [5][6][7] and DNA-based biosensing method [8][9][10][11][12][13][14][15][16] have been promoted and applied in the detection of C. sakazakii. Protein-based immunoassays, such as enzyme-linked immunosorbent assays (ELISAs) [5] and lateral flow immunoassays [6], are based on antibody-antigen interactions, which require a certain concentration of targets in samples, and sometimes cannot be applied in the detection at an early infection stage.…”
Section: Introductionmentioning
confidence: 99%
“…Some other methods that are classified into protein-based biosensing method [5][6][7] and DNA-based biosensing method [8][9][10][11][12][13][14][15][16] have been promoted and applied in the detection of C. sakazakii. Protein-based immunoassays, such as enzyme-linked immunosorbent assays (ELISAs) [5] and lateral flow immunoassays [6], are based on antibody-antigen interactions, which require a certain concentration of targets in samples, and sometimes cannot be applied in the detection at an early infection stage. DNA-based methods including polymerase chain reaction (PCR)-based biosensing methods [8,9], fluorescence biosensing Sensors 2023, 23, 4396 2 of 14 methods [10,11], colorimetric biosensing methods [12,13], and electrochemical biosensing methods [14][15][16] have been intensively promoted and investigated for the detection of C. sakazakii.…”
Section: Introductionmentioning
confidence: 99%